A Panel Analysis of the Impact of Green Transformation and Globalization on the Labor Share in the National Income - Małgorzata Gawrycka (MDPI AG, 2021)
This study aims to examine the impact of green transition and globalization processes on changes in the labour share. The study covers 76 national economies diversified in development, global production share and energy transition stage from 2000 to 2018. Based on the Total Economy Database data, panel models of the relationship between green transition, globalization and the labour share in the national income were estimated. The conducted Breusch–Pagan and Hausman tests proved the validity of using fixed-effects models. We confirmed the research hypothesis that the openness of the economy contributes to a decline in the labour share. The openness of the economy resulting from globalization reduces the labour share in the national income. We do not confirm hypotheses that suggest energy transition contributes to a reduction in the labour share and that the labour share will decline in the post-crisis period due to the lower bargaining power of workers. Changes in the labour share should be of interest to government representatives who influence the shape and implementation of economic policy, especially in employment policy, education, and investment policy, mainly aimed at the green transformation.